2009
DOI: 10.1111/j.1745-4549.2008.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF INSTANT GARCINIA (GARCINIA ATROVIRIDIS) TOM-YUM MIX AS A HIGH ACID SEASONING

Abstract: Commercial instant Tom‐Yum mixes that are currently marketed compare unfavorably in taste and aroma with freshly prepared soup. By comparing an experimental garcinia Tom‐Yum with traditional ingredients and a commercial mix, this study evaluated the total phenolic content and antioxidant activity of herbs and spices used in preparation, and compared consumer preference. The galangal methanolic extract had the highest total phenolic content and antioxidant activity, while the garcinia methanolic extract was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Rekha et al (2010) prepared a soup mix containing dill leaf and reported that TPC of its aqueous extract was 1.70 mg GAE/g mix. Tom-Yum, a popular commercially available Thai soup, containing several herbs and spices which contribute to its antioxidants was found to indicate TPC (in 30% v/v methanolic extract) as 1.50 mg GAE/g of dry mix (Siripongvutikorn et al 2009). Thus, the soup mix in the present study is at par with these reported values.…”
Section: Total Phenolics and Antioxidant Capacitymentioning
confidence: 99%
“…Rekha et al (2010) prepared a soup mix containing dill leaf and reported that TPC of its aqueous extract was 1.70 mg GAE/g mix. Tom-Yum, a popular commercially available Thai soup, containing several herbs and spices which contribute to its antioxidants was found to indicate TPC (in 30% v/v methanolic extract) as 1.50 mg GAE/g of dry mix (Siripongvutikorn et al 2009). Thus, the soup mix in the present study is at par with these reported values.…”
Section: Total Phenolics and Antioxidant Capacitymentioning
confidence: 99%
“…The popularity of tom yum soup could be seen in the presence of tom yum essence in various products, such as instant noodles, snacks, frozen tom yum products [3], and dried seasoning [4], [5]. Today, tom yum soups and tom yum flavored products could be seen in various shelf spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Tom-Kha or galangal coconut milk soup has been classified as the sixth order of top ten Thai cuisines due to its mild taste, sweet and sour flavor [4]. In general, the ingredient of Tom-Kha soup consists of herbs and spices such as galangal rhizome, lemon grass, kaffir lime leaves and chili have been reported as natural antimicrobial agents [5,6] and antioxidants [7][8][9][10][11]. Cooking procedure a coconut milk about 50% of soup is recommended to add [8].…”
Section: Introductionmentioning
confidence: 99%